"There is nothing more permanent than something temporary": historical retrospective of Siberian water infrastructure projects; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Ageev I. A. Iliya Aleksandrovich (2016, 2016)
Title screen